Evaluation of Socioeconomic Determinants of Quality of Life among Healthcare Providers (Asian Journal of Pharmaceutics (AJP), 2020)
Background: In literature, fewer studies are evident that quality of life (QoL) among healthcare providers (HCPs)is a paramount concern, especially to have optimum and best patient care. If the QoL of the HCPs is not up to thesatisfactory level, it will have a direct effect on QoL of their patients. Objective: This study aimed to determinesocioeconomic determinants of QoL among HCPs in Malaysia. Materials and Methods: A cross-sectional studywas conducted using among HCPs using World Health Organization QoL-BREF using a convenience samplingmethod. The socioeconomic determinants of QoL among HCPs were determined using descriptive and inferentialstatistics. Data were entered and analyzed using Statistical Package for the Social Sciences ver. 24.0. Results: Outof total (n = 310) studied HCPs, more females (n = 188, 60.6%), than males (n = 122, 39.4%) participated in thisstudy. According to the study findings, in the psychological domain, marital status, in social domain marital statusand job nature, and in environmental domain experience were observed as pure socioeconomic determinants thatshowed statistically significant values (P < 0.05). Conclusion: In Malaysia, overall, the HCPs had better QoL andhad good access to excellent healthcare services, self-confidence, and social life.